2007
DOI: 10.1637/0005-2086(2007)51[668:mrfvda]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Rt-PCR for Virulence Detection and Differentiation Between Newcastle Disease Virus and Goose-Origin APVM-1

Abstract: Newcastle disease virus (NDV) belongs to the Paramyxoviridae family and has had a great impact on the poultry industry. In the past, NDV strains were generally pathogenic only to fowls, but goose paramyxovirus (goose-origin APVM-1) is highly infectious to waterfowl, and, thus, there have been frequent outbreaks in China since 1997. In this study three pairs of specific primers were designed to detect the virulence of different NDV and goose-origin APVM-1 isolates and to differentiate between NDV and goose-orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The close phylogenicity of the goose-originated NDVs and concurrent epidemic chicken-originated NDVs has also been mentioned in other reports [18,25,26]. In contrast, Kong et al demostrated the genetic difference between the chicken- and goose-originated NDVs, and used this information to establish a multiplex RT-PCR method for the differentiation between the chicken- and goose-originated genotype VIId NDVs [27]. In addition, Li et al showed antigenic variation between genotype VIId NDV of goose-origin and an early lineage strain of genotype IX NDV from chicken[28].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The close phylogenicity of the goose-originated NDVs and concurrent epidemic chicken-originated NDVs has also been mentioned in other reports [18,25,26]. In contrast, Kong et al demostrated the genetic difference between the chicken- and goose-originated NDVs, and used this information to establish a multiplex RT-PCR method for the differentiation between the chicken- and goose-originated genotype VIId NDVs [27]. In addition, Li et al showed antigenic variation between genotype VIId NDV of goose-origin and an early lineage strain of genotype IX NDV from chicken[28].…”
Section: Introductionmentioning
confidence: 81%
“…Therefore, it is unlikely to differentiate the chicken- and goose-originated NDVs based on their genomic sequences. We noted that Kong et al developed a PCR method to distinguish between chicken- and goose-originated VIId NDVs on the basis of genomic differences they found between the two NDV groups [27]. One explanation for the discrepancy is that they used only a few goose-originated strains in their study.…”
Section: Discussionmentioning
confidence: 99%
“…23,87 The most unifying histologic feature is severe necrosis of the lymphoid tissues scattered throughout the body, most especially prominent in spleen and gut-associated lymphoid tissue, which corresponds to the foci hemorrhage and ulceration noted grossly. 9,23,64,67,110,119 In the less severe, or initial stages, there is lymphoid depletion and hyperplasia of macrophages with large vacuolated cytoplasm (commonly referred to as the "starry-sky" effect). In later stages, there is accumulation of cellular and karyorrhectic debris, pyknosis, and numerous macrophages with vacuolated cytoplasm that contain nuclear debris (tingible body macrophages).…”
Section: Clinical Signs and Pathologic Findings With Ndv Infectionmentioning
confidence: 99%
“…In order to detect strains responsible for false-negative results in the molecular assays, alternative and strain-specific RT-PCR or real-time RT-PCR were developed, particularly for the genetically divergent pigeon paramyxoviruses (PPMV-1) 18 and APMV-1 of goose-origin. 67 Modifications of existing F gene-targeting protocols by the insertion of degeneracy in the oligonucleotides employed in the assays were considered 57 as well as a completely novel F-gene probe applied to a preexisting USDA-validated protocol. 103 Also, different approaches to the amplification of the F gene have been attempted, such as the development of real-time RT-PCR using combination of distinct, shorter minor groove binder (MGB) probes within the same reaction mix 37 or the insertion of nucleotide degeneracy and locked nucleotides (LNA) in the probes.…”
Section: Real-time Pcr Era Of Detection and Typing Of Apmv-1mentioning
confidence: 99%
“…Against the most prevalent viral pathogens circulating in goose, like Goose parvovirus (GPV), Newcastle disease virus (NDV), goose herpesvirus (GHV), and goose adenovirus (GAV), several molecular assays have been developed for clinical diagnosis in the past few years by using either genomic detection methods such as PCR or antigen detection methods such as ELISA ( Chen et al, 2009 ; Guo et al, 2009 ; Wan et al, 2019 ; Wu et al, 2019 ; Tomar et al, 2021 ). Also, several duplex detection assays were developed for rapid screening of multiple pathogens, usually by duplex PCR ( Kong et al, 2007 ; Chen et al, 2013 ; Wang et al, 2020 ). These methods have brought great convenience and benefits to the breeding industry.…”
Section: Introductionmentioning
confidence: 99%